2003
DOI: 10.1034/j.1399-0012.2003.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Segmental glomerulosclerosis in IgA nephropathy after renal transplantation: relationship with proteinuria and therapeutic response to enalapril

Abstract: Significant proteinuria was associated with advanced chronic injury, especially with the presence of SS in Tx-IgAN, but anti-proteinuric effect of enalapril was not affected by graft histology. It remains to be clarified whether glomerular mesangial expansion plays a role in graft dysfunction in a subset of Tx-IgAN showing prominent mesangial changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…11 With the limited information on recurrent IgAN, we previously conducted a study of post-transplant IgAN (TxIgAN), incorporating glomerular mesangial IgA deposits irrespective of original disease confirmation, to reveal histological features associated with proteinuria. The current study showed an association between proteinuria and segmental glomerulosclerosis, 12 which was in accord with a study from Japan. 13 However, in contrast to their study which revealed no crescents, 13 glomerular crescents were found in renal allograft biopsies in four of 54 patients at an average of 46 months post-transplant, and they all accompanied urinary abnormality.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…11 With the limited information on recurrent IgAN, we previously conducted a study of post-transplant IgAN (TxIgAN), incorporating glomerular mesangial IgA deposits irrespective of original disease confirmation, to reveal histological features associated with proteinuria. The current study showed an association between proteinuria and segmental glomerulosclerosis, 12 which was in accord with a study from Japan. 13 However, in contrast to their study which revealed no crescents, 13 glomerular crescents were found in renal allograft biopsies in four of 54 patients at an average of 46 months post-transplant, and they all accompanied urinary abnormality.…”
supporting
confidence: 92%
“…13 However, in contrast to their study which revealed no crescents, 13 glomerular crescents were found in renal allograft biopsies in four of 54 patients at an average of 46 months post-transplant, and they all accompanied urinary abnormality. 12 The aim of the present study was to examine the prevalence and significance of glomerular crescents in chronic graft dysfunction of TxIgAN patients.…”
mentioning
confidence: 98%
“…The presence of segmental sclerosis but not mesangial proliferation was associated with proteinuria of 1 g or more per 24 h in recurrent samples. Considering the average time to posttransplantation biopsy (3.6 years) and the low prevalence of chronic rejection, it seems that glomerular hypertrophy [23] and segmental glomerulosclerosis are major factors in the development of proteinuria in patients with recurrent IgAN. Of recurrent IgAN patients, 63.6% were treated with angiotensin-converting enzyme inhibitors or receptor blockers at the time of biopsy, which could have affected urinary protein excretion [21,24].…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available about therapeutic trials in patients with post‐transplant IgAGN recurrence. Some investigators (36, 37) found an important antiproteinuric effect of ACE inhibitors in IgAGN transplant recipients. As proteinuria is considered an important marker of progression in transplant patients with IgAGN (38), it is possible to speculate that ACE inhibitors and/or angiotensin receptor blockers could slow the progression of recurrent glomerulonephritis.…”
Section: Potential Treatments For Recurrent Igagnmentioning
confidence: 99%